MODEL OF CLOUD ORIENTED LEARNING ENVIRONMENT (COLE) OF COMPREHENSIVE EDUCATIONAL ESTABLISHMENTS (CEE) TEACHER - Lytvynova, S. (Journal of Information Technologies in Education (ITE), 2015)
The rapid development of cloud services, their introduction into the system of secondary education requires the implementation of balanced pedagogical models for their mobility and optimal use during the learning process. The article analyzes the current requirements for the learning environment, highlights the problems of pedagogical modeling and use of teacher’s cloud oriented learning environment in the system of comprehensive educational establishments, analyzes the notion «model», «modeling», it is determined such definitions as services’ «internal» and «external integration», «structural –integrative» model. There are described the requirements to the model, developed the base model of teacher’s cloud oriented learning environment, which is based on the following components: system of websites, emails, bank of teaching materials, blogs, document repository, an internal social network, study groups, calendars, conference call. This model can be a base for the comprehensive educational establishments of all types and forms of education, it gives a complete picture of the COLE’s possibilities for teacher, it gives reasonable detailization for understanding the important processes within COLE, as well as provides educational mobility, communication, cooperation, teacher’s collaboration with all participants of educational process.